Microstructure, dielectric and piezoelectric properties of 0–3 lead free barium zirconate titanate ceramic-Portland fly ash cement composites - Phakin Chomyen (2018)
© 2017 Elsevier Ltd and Techna Group S.r.l. Piezoelectric ceramic – Portland cement composites have been developed for sensor application in concrete structures to overcome the acoustic matching problem that may occur for piezoelectric ceramic or polymers with concrete. Pozzolanic materials such as fly ash are commonly used in concrete to enhance durability. The objectives of this research were to investigate the effects of fly ash addition on the physical properties, dielectric properties and piezoelectric properties of 0–3 barium zirconate titanate ceramic– Portland cement composites. The results showed that the dielectric constant of these composites decreased when the fly ash content in the composite increases. However, the piezoelectric coefficient (d33) value of BZT–PC composite with fly ash 10% by volume was found to be similar to that of BZT–PC composites.